A Proposal of Mercury Removal Technique for Oil and Gas Industrial Wastewater - Abdul Rashid, Nurun Najihah (Universiti Teknologi PETRONAS, 2017)
The purpose of this study is to propose the most practical and reasonable technique to remove mercury from the oil and gas industrial wastewater. Researches has been shown that there were a lot of techniques that could be implemented by the oil and gas industry to remove mercury from their waste streams. However insufficient researches had been conducted to evaluate the suitability and sustainability of the techniques to the application of oil and gas plant. Therefore, this project analyses numerous techniques that are possibly having high suitability with the plant’s operation and to fulfil the Malaysia regulated requirement for the industrial effluent discharge standards. Based on review of 116 research papers, mercury removal techniques were accumulated and evaluated using Decision Matrix Analysis tool. The mercury removal techniques were assessed based on a set of criteria, e.g. mercury removal percentage, time and cycle of treatment, original mercury concentration in wastewater, and effective range of temperature for mercury removal.